Subungual squamous cell carcinoma with metastasis to the femur, multiple lymph nodes, adrenal glands, and lungs - B, de Cecco; PVM, de Oca; IM, Langohr; B, Boudreaux; E, Sasaki (Brazilian Journal of Veterinary Pathology, 2023)
A 9-year-old intact male Rottweiler with clinically suspected prostatic mass had difficulty climbing stairs. The dog was also favoring the left hind limb. The owners mentioned that he had started to act quieter and exhibit declining appetite with weight loss over the course of 2 weeks, in addition to having hematuria. Numerous pulmonary nodules and an abdominal mass with displaced urinary bladder and colon were evident on radiographs. In addition, lytic bone, with cortical bone disruption, was identified in the mid-diaphyseal region of the left femur. Marked lymphadenomegaly of the left popliteal and inguinal nodes was identified on physical examination. A year prior to the onset of these clinical signs, the patient had undergone amputation of digit 5 of its left hind limb due to a severely ulcerated lesion, diagnosed histologically as a subungual malignant neoplasm. An oral tumor between teeth 206 and 207 was also removed; however, this mass was not evaluated histologically.